Analysis of Diet in Daśakumāracarita - devi, Sonika; Yadav, Sudama Singh; Goswami, PK; Yadav, Virendra; Rajauriya, Jaivir Singh; Ansari, MD Shahid; Singh, Priya (Journal of Neonatal Surgery, 2025)
Mahākavi Daṇḍin’s Daśakumāracarita is a significant piece of Sanskrit prose literature that portrays the social, cultural, and moral life of early medieval Indian culture realistically and vividly. In addition to recounting the valiant lives of the ten Kumars, this book gently conveys the way of life, behaviours, and ideals of the era's society.In Daśakumāracarita, food is shown as both a bodily requirement and a sign of cultural refinement, social elegance, and moral worth. The food and eating practices discussed in the book have been thoroughly examined from a social and moral perspective in this paper.This study demonstrates that food is not only a means of subsistence but also a useful tool for comprehending society, lifestyle, and values in Sanskrit literature through a coordinated approach of text-analysis, socio-cultural interpretation, and moral evaluation.